The Role and Importance of Self-Awareness and Assessment in A Person's Life - Avezova Bakhtigul Kholmurotovna (Web of Scientist International Scientific Research Journal, 2025)
This study examines the role of self-awareness and self-assessment in shaping an individual’s personality, decision-making, and psychological well-being. The research aims to analyze the process of self-awareness development, its impact on self-evaluation, and how it influences personal growth and professional success. A qualitative methodology is employed, incorporating psychological theories, literature review, and observational studies to explore the stages of self-awareness from early childhood to adulthood. The findings highlight that self-awareness allows individuals to regulate their emotions, develop confidence, and enhance their ability to make rational decisions. The study also categorizes self-assessment into adequate, high, and low levels, demonstrating the consequences of overconfidence or self-doubt in personal and social interactions. Realistic self-assessment fosters balanced emotional health and effective decision-making, whereas extreme self-perception can lead to stress, failure, or lack of motivation. The research concludes that continuous self-reflection and self-regulation are key to personal and professional development. Encouraging realistic self-awareness from an early age can help individuals build resilience and maintain a positive self-concept, ultimately contributing to a well-balanced and successful life.